Acute physiological, perceived exertion and enjoyment responses during a 4-week basketball training: a small-sided game vs. high-intensity interval training - Zeng, Jinshu; Pojskic, Haris; Xu, Jing; Xu, Yuanhong; Xu, Fei (Frontiers in Psychology, 2023)
Objective: Although previous research found that small-sided game (SSG) training was more enjoyable than high-intensity interval training (HIT) in various sports, no data were provided during longer training period in basketball. Thus, this study aimed to examine the acute physiological, perceived exertion and enjoyment responses during 4-week progressive basketball SSG or HIT programs. Methods: Nineteen female collegiate basketball players were randomly assigned to SSG (n=9) and HIT (n=10) group that performed either SSG or HIT 3 times per week for 4 weeks during the pre-season. Average and percentage of maximal heart rate (HRmean and %HRmax), rating of perceived exertion (RPE), and physical activity enjoyment (PACES) were determined during each training session. Results: SSG had higher PACES than HIT in each week (p < 0.05). There were no significant interactions or main group effects in HRmean, %HRmax or RPE. In the SSG group, although no significant differences were found in HR responses, %HRmax was below 90% in week 1 and week 2. Accompanied with changes in %HRmax, RPE in week 1 and week 2 was lower than that in week 3 and week 4 (p < 0.05). Conclusions: Our findings suggest that SSG and HIT elicit similar acute HR response and RPE level, but SSG is perceived as more enjoyable and therefore it is more likely to increase exercise motivation and adherence comparing to HIT. Moreover, it seems that half-court, 2vs.2 SSG training format with modified rules and lasting ≥7.5 minutes should be prescribed as an enjoyable training alternative to provide optimal cardiovascular stimuli (>90% of HRmax) for female basketball players.